(untitled) (Journal of Contemporary Philology, 2019)
This article was motivated by the need to highlight the various facets of present-day research on pragmatic markers in view of the academic recognition of their importance in conversation. The aim of the paper is twofold. First, it reviews the current literature on pragmatic markers focusing on their definition, classification, functions, and main features as discussed in .ithered а верзија, со црно- поправенатапрвата реченица) види дали ти се допаѓа. different theoretical frameworks The paper also addresses issues that may cause confusion in the study of pragmatic markers, such as word class membership, terminological uncertainty, multifunctionality and domains of application. Second, the paper aims to encourage research on pragmatic markers in Macedonian: in particular to enhance cross-cultural research of these markers by inclusion of other languages and to promote the study of pragmatic markers in the interlanguage of Macedonian learners of foreign languages. The article provides a useful bibliography of the studies on pragmatic markers and refers to major cross-cultural and interlanguage studies including those in the field of South Slavic languages.